The role of gut microflora dysbiosis in clinical manifestation of patients with non-alcoholic fatty liver disease and non-alcoholic steatohepatitis. (International Journal of Scientific Research and Management (IJSRM), 2022)
Background and aim: The aim of this study was to evaluate the role of gut microbiota with wide variety of clinical manifestations of patients with non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH). Methods: The study enrolled 133 cases of patients with NAFLD/NASH who were diagnosed at Enmedic Clinic, Tbilisi/Georgia and carried out between May 2017 and May 2021. Patients were 21-65 years of age attending our clinic. Patients were diagnosed with NASH/NAFLD based on fibroscan of liver and ultrasound investigation, and additionaly for NASH with raised serum alanine aminotransferase (ALT) and aspartat aminotrasnferase (AST) levels greater than upper limit of normal (40 IU/ ml). Trial profile of patients is shown on figure 1. 10 patients loss follow up The 123 patients were divided into three groups. Group A (61 patients) was diagnosed with NAFLD, the 42 patients of group B were diagnosed with NASH and group C (control) were 20 healthy volunteers. Results: Family Enterobacteriaceae, family Lactobacillaceae, and genus Bacteroides like Streptococcus were increased in patients with NAFLD/NASH compared with controls, also uncultured Clostridiales as well as entero-hemolytic Escherichia Coli were increased, whereas genus Faecalibacterium, and genus Bifidobacterium as well as hemolytic Enterococcus faecalis were decreased in patients with NAFLD/NASH. Significant loss of beneficial bacteria for intestinal barrier function like Faecalibacterium was observed. The diversity of the microbiota was decreased in patients compared with controls. Conclusions: This study found that the gut microbiota play a large role in the development of NAFLD/NASH. NAFLD developed in the initially in patients with significant dysbiosis. It suggests also that the gut microbiome correction may be beneficial for the treatment of patients with NAFLD/NASH.